Otoprotection to Implanted Cochlea Exposed to Noise Trauma With Dexamethasone Eluting Electrode - Eshraghi, Adrien A.; Wolfovitz, Amit; Yilmazer, Rasim; Garnham, Carolyn; Yilmazer, Ayca Baskadem; Bas, Esperanza; Ashman, Peter; Roell, Jonathan; Bohorquez, Jorge; Mittal, Rahul; Hessler, Roland; Sieber, Daniel; et al. (Frontiers in Cellular Neuroscience, 2019)
Cochlear implantation (CI) is now widely used to provide auditory rehabilitation to individuals having severe to profound sensorineural hearing loss. However, CI can lead to electrode insertion trauma (EIT) that can cause damage to sensory cells in the inner ear resulting in loss of residual hearing. Even with soft surgical techniques where there is minimal macroscopic damage, we can still observe the generation of molecular events that may initiate programmed cell death via various mechanisms such as oxidative stress, release of pro-inflammatory cytokines, and activation of the caspase pathway. In addition, individuals with CI may be exposed to noise trauma (NT) due to occupation and leisure activities that may affect their hearing ability. Recently, there has been an increased interest in the auditory community to determine the efficacy of drug eluting electrodes for the protection of residual hearing. The objective of this study is to determine the effect of NT on implanted cochlea as well as the otoprotective efficacy of dexamethasone eluting electrode to implanted cochlea exposed to NT in a guinea pig model of CI. Animals were divided into five groups: EIT with dexamethasone eluting electrode exposed to NT; EIT exposed to NT; NT only; EIT only and naïve animals (control group). The hearing thresholds were determined by auditory brainstem recordings (ABRs). Cochlea were harvested and analyzed for transcript levels of inflammation, apoptosis and fibrosis genes. We observed that threshold shifts were significantly higher in EIT, NT or EIT+NT groups compared to naive animals at all the tested frequencies. The dexamethasone eluting electrode led to a significant decrease of hearing threshold shifts in implanted animals exposed to NT. Proapoptotic (TNFα, TNFαR1a) and pro-fibrotic (TGFβ) genes were more than two fold up-regulated following EIT and EIT+NT compared to the control group. The use of dexamethasone releasing electrode significantly decreased the transcript levels of pro-apoptotic and pro-fibrotic genes. The dexamethasone releasing electrode has shown promising results for hearing protection in implanted animals exposed to NT. The results of this study suggest that dexamethasone releasing electrode holds a great potential in developing effective treatment modalities for NT in implanted cochlea.